Functional leaf anatomy of the invasive weed Solanum rostratum Dunal. (3rd March 2022) - Abu‐Nassar, Jackline; Gal, Shira; Shtein, Ilana; Distelfeld, Assaf; Matzrafi, Maor
Abstract: Solanum rostratum Dunal is an aggressive invasive weed invading many countries worldwide. Our previous study indicated differences in herbicide response between young and mature plants. In this study, we explore the functional leaf surface anatomy of S . rostratum . Leaf area surface characterisation was performed by counting stomata, stellate and glandular trichomes on upper and lower leaf sides on scanning electron microscopy (SEM) micrographs. Total cuticular waxes were extracted and weighed in young and mature leaves. Young and mature leaves were tested for water permeability of the epidermal surfaces using the apoplastic tracer Calcofluor. S . rostratum plants were sprayed with luminous trace colour solution with and without 1% surfactant, droplet number and area were calculated. In young S . rostratum leaves, the leaf surface was densely covered with stellate trichomes on both leaf sides; however, in the mature leaf, stellate trichomes density became low, and prickle rigid increased in mature leaves. Wax amount was significantly higher in mature leaves, while number of stomata was higher in young leaves. Young leaves showed high leaf permeability, with the fluorescent dye permeating the leaf staining the vascular bundles. In young and mature leaves treated with a spraying solution with the addition of surfactant, low droplet number alongside higher coverage area was recorded. Our data highlight the notable differences in leaf epidermal structure of young versus mature plants. We conclude that differences in herbicide permeability, water loss and herbivory in young versus mature leaves of S . rostratum are governed by variation in leaf functional anatomy.